Guidance on Making Tea Bags from Kersen Leaves for The Residents of Rt 05 Rw 05, Lamper Tengah Subdistrict, Semarang City - Agus Sudarmanto; Joko Budi Poernomo; Andi Fadllan; Andi Ismail (Konsorsium Pengetahuan Innoscientia (KOPINNOS), 2025)
Tea is a beverage that contains caffeine, an infusion made by brewing leaves, leaf buds, or leaf stems. Kersen, also known as talok (Muntingia calabura), is a type of tree with small, sweet, bright red fruits. In addition to its edible fruits, the leaves can also be used as an ingredient for beverages. Kersen leaves have antiseptic and antibacterial properties, making them useful for boosting the immune system and treating various illnesses. For this reason, our team intends to provide assistance in producing tea from kersen leaves for the residents of RT 05 RW 05, Lamper Tengah Subdistrict, Semarang City. The stages of this community service program include: (1) Socialization of the benefits of kersen leaves; (2) Training; (3) Monitoring and mentoring.The impacts of this program include: (1) PKK women’s group members of RT 05 RW 05, Lamper Tengah Subdistrict gain knowledge about the benefits of kersen leaves; (2) Improved knowledge and skills in processing kersen leaves into tea bags; (3) Increased entrepreneurial motivation among PKK women’s group members of RT 05 RW 05.